2020
DOI: 10.1186/s12905-020-01016-3
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive capacity and recurrence of disease after surgery for moderate and severe endometriosis – a retrospective single center analysis

Abstract: Background Endometriosis can be associated with considerable pain and sterility. After surgical excision of moderate or severe endometriosis lesions, the rate of recurrence reaches up to 67%. The objective of this retrospective study was to establish the recurrence and pregnancy rates following surgical resection of stage III/IV endometriosis lesions. Indications for operation were endometriosis symptoms, sonographic findings and/or infertility. Methods A total of 456 p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The postoperative pregnancy rate in the LS group, including the postoperative pregnancy rate of infertility patients, was significantly higher than the LT group, indicating that LS treatment of EM can significantly improve infertility. Schippert et al ( 16 ) reported that 74.3% (52/70) of women became pregnant after LS for EM, and 61.3% (19/31) became pregnant after LT; 42.1% (8/19) became pregnant after switching from LS to LT. There was a statistically significant correlation between the postoperative conception rate and surgical approach ( P = 0.00893).…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative pregnancy rate in the LS group, including the postoperative pregnancy rate of infertility patients, was significantly higher than the LT group, indicating that LS treatment of EM can significantly improve infertility. Schippert et al ( 16 ) reported that 74.3% (52/70) of women became pregnant after LS for EM, and 61.3% (19/31) became pregnant after LT; 42.1% (8/19) became pregnant after switching from LS to LT. There was a statistically significant correlation between the postoperative conception rate and surgical approach ( P = 0.00893).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the patients in the present study underwent surgery for the management of endometriosis. The extent of surgical procedures is based on the age of the patient and the desire for fertility preservation [61]. Moreover, adjuvant pharmaceutical therapy was administered to 16 patients postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adjuvant pharmaceutical therapy was administered to 16 patients postoperatively. A favorable effect of postoperative medication maintenance therapy has been reported for symptomatic relief and recurrence prevention, but its exact role still remains controversial [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Patients are classified by taking into account the presence of posterior cul-de-sac obliteration, location and site of implants, density of adhesions, and location of adhesions. 20,21…”
Section: Diagnosismentioning
confidence: 99%